Improving the Quality of Qur’an Learning Through the Ummi Method - Kurniawan, Bambang Dwi; Ikhwan, Afiful; Setiawan, Wahyudi; Redho Syam, Aldo; Kholij Zukhrufin, Fina (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2025)
This study aims to describe the improvement of the quality of Al-Qur'an learning through the Ummi method at the Islamic Elementary School-Madrasah Ibtidaiyah (MI) of Pesantren Anak Soleh (PAS) Baitul Qur'an, Gontor, Ponorogo. The study used a qualitative approach with data collection techniques in the form of interviews with the principal, the coordinator of the Koran reading, and the Al-Qur'an teacher, as well as observation and documentation of learning activities. Data analysis applied the Miles and Huberman model, which includes data reduction, data presentation, verification, and conclusion. Data validity testing was carried out using credibility, dependability, transferability, and confirmability techniques. The results of the study showed that the improvement of the quality of Al-Qur'an learning through the Ummi method was influenced by three main factors: (1) implementation of the Ummi Foundation policy, including the active involvement of the principal in learning, providing motivation to teachers and students, and appointing an activity coordinator; (2) determination of the Al-Qur'an learning curriculum starting from Volume 1 to Volume 6, continued with tadarus up to Juz 5, tahfidz Juz 29 and 30, teaching gharib, tajwid, and turjuman; and (3) application of learning models, namely private learning with one teacher and one student, classical reading-listening learning with one teacher and twelve students, and pure classical reading-listening learning with one teacher and eight students. These findings confirm that the Ummi method can effectively improve the quality of Al-Qur'an learning in Islamic boarding schools.